Fire-resistant material and refractory material using the same, and method for manufacturing fire-resistant material
Patent Information
- Application Number
- JP2025058324
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0013】 このように、本発明に従う耐火材料にあっては、アルミニウムドロスを用いて調製された混合物の焼成物にて構成され、かかる焼成物は、Al2O3及びMgOを化学成分として各々、所定割合にて含有する一方で、結晶相としてペリクレース相を含有しないものである。このような構成によって、本発明の耐火材料は、耐火材料としての耐消化性に優れていると共に、アルミニウム鋳造の際に用いられる種々の容器の内張り材等として使用される耐火物において使用した場合に、かかる耐火物が、アルミニウム溶湯の耐浸透性において優れた特性を発揮することとなるのである。
Smart Images

Figure 2026165760000001 
Figure 2026165760000002 
Figure 2026165760000003
Abstract
Description
Technical Field
[0001] The present application relates to a refractory material, a refractory using the same, and a method for producing the refractory material, and particularly relates to a refractory material that has excellent hydration resistance as a refractory material and is suitably used in refractories employed as lining materials for various containers used in aluminum casting and the like.
Background Art
[0002] Aluminum dross, also referred to as aluminum ash, is an impurity (slag) formed on the surface of a molten metal when aluminum ingots or aluminum-containing scraps are melted in the manufacturing process of aluminum products and the like. Although such aluminum dross contains a large amount of reusable metallic aluminum, at present, part of it is utilized as a resource, but most of it is disposed of as industrial waste. In recent years where storage and disposal sites for industrial waste tend to be insufficient, development of technologies related to effective utilization of aluminum dross has been desired.
[0003] For example, Patent Document 1 (Japanese Unexamined Patent Publication No. 2000-263013) and Patent Document 2 (Japanese Unexamined Patent Publication No. 2000-263014) propose a method of using aluminum dross residual ash obtained by recovering metallic aluminum from aluminum dross generated during aluminum refining, in which the aluminum dross is calcined and then used as a raw material for an alumina-spinel castable refractory or as a raw material for an alumina-magnesia castable refractory. Further, Patent Document 3 (Japanese Unexamined Patent Publication No. 2024-110580) discloses a detoxification treatment method for aluminum dross, which is characterized in that Al and AlN contained in the aluminum dross are subjected to an oxidation reaction to cause combustion synthesis in an atmosphere with an oxygen concentration of 40% by volume or more, so as to detoxify the aluminum dross.
Prior Art Documents
Patent Documents
[0004] [Patent Document 1] Japanese Patent Publication No. 2000-263013 [Patent Document 2] Japanese Patent Publication No. 2000-263014 [Patent Document 3] Japanese Patent Publication No. 2024-110580 [Overview of the project] [Problems that the invention aims to solve]
[0005] Under these circumstances, the inventors diligently investigated the effective utilization of aluminum dross and discovered that a mixture of aluminum dross and magnesia source raw materials, obtained by firing under predetermined conditions, has excellent fire resistance as a refractory material. Furthermore, when such a refractory material is used as a lining material for various containers used in aluminum casting, it exhibits excellent resistance to penetration by molten aluminum. Based on these findings, the present invention was completed.
[0006] In other words, the present invention was made against this backdrop, and its objective is to provide a refractory material that is excellent in fire resistance as a refractory material and is suitable for use as a lining material for various containers used in aluminum casting. Furthermore, the present invention also aims to provide a refractory material made using such a refractory material that exhibits excellent properties, and an advantageous method for manufacturing refractory materials. [Means for solving the problem]
[0007] Furthermore, in order to solve the above-mentioned problems, the gist of the present invention is a refractory material comprising a calcined product of a mixture prepared using aluminum dross, characterized in that the calcined product contains 60.0 to 90.0% by mass of Al2O3 and 5.0 to 30.0% by mass of MgO as chemical components, and does not contain a periclase phase as a crystalline phase.
[0008] In a preferred first embodiment of the refractory material according to the present invention, the fired product is alumina-rich spinel or spinel.
[0009] Furthermore, in a preferred second embodiment of the refractory material according to the present invention, the impurity content is 10.0% by mass or less.
[0010] On the other hand, the present invention also encompasses refractories made using mixtures containing the refractory materials described in each of the above embodiments.
[0011] In addition, the present invention also includes a method for manufacturing a refractory material according to each of the above embodiments, comprising the steps of: wet grinding a mixture consisting of aluminum dross, a magnesia source raw material, and water to produce a slurry; dewatering the slurry to obtain a clay-like substance, and then using this clay-like substance to produce a molded product according to an extrusion molding method; drying the molded product; and firing the dried molded product at 1550 to 1700°C using a rotary kiln.
[0012] In the method for producing a refractory material according to the present invention, preferably, the proportion of aluminum dross in the mixture is 60 to 90% by mass. [Effects of the Invention]
[0013] Thus, the refractory material according to the present invention is composed of a calcined product of a mixture prepared using aluminum dross, and such calcined product contains Al2O3 and MgO as chemical components in predetermined proportions, while not containing a periclase phase as a crystalline phase. With this configuration, the refractory material of the present invention has excellent fire resistance as a refractory material, and when used as a refractory material for lining various containers used in aluminum casting, such a refractory material exhibits excellent resistance to penetration by molten aluminum. [Modes for carrying out the invention]
[0014] Incidentally, the refractory material according to the present invention consists of a calcined product of a mixture prepared using aluminum dross. Such a calcined product contains 60.0 to 90.0% by mass of Al2O3 and 5.0 to 30.0% by mass of MgO as chemical components, while not containing a periclase phase as a crystalline phase. That is, the refractory material according to the present invention mainly consists of Al2O3 and MgO as chemical components. If the Al2O3 content is too low, the MgO content will inevitably increase. If a refractory material is manufactured by calcining a raw material containing aluminum dross in order to obtain a calcined product with a high MgO content, periclase will be formed as a crystalline phase in the resulting calcined product, and as a result, the fire resistance of the refractory material made from such a calcined product may deteriorate.
[0015] Furthermore, in the refractory material of the present invention, it is preferable that the content of impurities in the calcined product constituting the refractory material is 10.0% by mass or less. Examples of such impurities include various oxides that are inevitably contained in aluminum dross and magnesia source raw materials, specifically, various oxides such as calcium, silicon, sodium, potassium, iron, and titanium.
[0016] Furthermore, the apparent porosity of the refractory material according to the present invention is preferably 25.0% or less. In the present invention, refractory materials with an apparent porosity exceeding 25.0% have excellent fire resistance of the material itself, but when used as a raw material for refractories used in aluminum casting, there is a risk that the resistance to penetration of molten aluminum will not be sufficiently exhibited. In this specification and in the claims, "apparent porosity" means that it is measured in accordance with the "boiling method" described in JIS-R-2205 (1992).
[0017] Such fire-resistant materials according to the present invention can be manufactured according to various conventionally known methods, but advantageously, they can be manufactured according to the methods shown below.
[0018] First, a mixture is prepared as a raw material using aluminum dross and a magnesia source to obtain a calcined product containing 60.0 to 90.0% by mass of Al2O3 and 5.0 to 30.0% by mass of MgO as chemical components.
[0019] In this invention, the aluminum dross used is not particularly limited, and any impurities (slag) generated during aluminum smelting or the manufacturing process of aluminum products can be used without any particular limitations. In this invention, aluminum dross with an average particle size of 50 μm or less is preferably used, aluminum dross with an average particle size of 30 μm or less is more preferable, and aluminum dross with an average particle size of 10 μm or less is most preferably used.
[0020] Furthermore, any material that has been conventionally used in the manufacture of refractory aggregates, etc., can be used as a source of magnesia. Specifically, examples include natural magnesia, seawater magnesia, as well as magnesia clinker, magnesium hydroxide, and electrofused magnesia produced according to various known methods.
[0021] In producing the refractory material of the present invention, it is preferable to prepare the mixture as the raw material such that the content ratio of impurities contained in the finally obtained fired product (refractory material) is 10.0 mass% or less. By suppressing the content ratio of impurities contained in the fired product to a low level in this manner, the effects of the present invention can be more advantageously enjoyed. In the preparation of the raw material (mixture), it is also possible to use various raw materials conventionally used in the production of refractory aggregates and the like, as long as the object of the present invention is not impaired. Examples of raw materials that can be used in the present invention include calcined alumina, sintered alumina, fused alumina, and other alumina source raw materials.
[0022] Next, the mixture as the raw material prepared as described above is subjected to a pulverization treatment. As the method for the pulverization treatment, any of various conventionally known methods can be adopted, but a wet pulverization method is advantageously adopted in the present invention. When performing wet pulverization, water is added at a ratio of about 100 parts by mass relative to 100 parts by mass of the raw materials (aluminum dross, magnesia source raw material, others). Further, the wet pulverization is preferably carried out so that the average particle diameter of the aluminum dross after pulverization is 20 μm or less, more preferably 10 μm or less.
[0023] The slurry obtained by wet pulverization is dehydrated using a filter press to form a clay-like material. This clay-like material is subjected to extrusion molding using various extruders to produce an extrusion molded article. The shape of the die (extrusion port) of the extruder can be any shape such as a round shape, a star shape, a polygonal shape such as a cross shape, and the diameter of the die (extrusion port) is generally about 5 to 50 mm.
[0024] Then, after drying the obtained extruded molded body, the dried extruded molded body is fired at 1550 to 1700°C using a rotary kiln, whereby the target fired product is obtained. Here, if the firing temperature is lower than 1550°C, periclase is formed as a crystal phase in the fired product, and the presence of such periclase may degrade the slaking resistance as a refractory material. The firing time is appropriately set according to the scale of the rotary kiln and the like, and is usually about 30 minutes to 2 hours. The fired product obtained in this manner can be used as it is as a refractory material without any other processing, but a pulverization treatment is carried out as necessary.
[0025] The refractory material produced as described above is used by being blended into refractory raw materials in the same manner as conventional refractory materials, when producing various refractories (shaped refractories, unshaped refractories, etc.). Examples of the refractory raw materials include those containing Al₂O₃ (alumina) as a main component, for example, raw materials that give chemical compositions such as alumina-silica (SiO₂) type, alumina-magnesia type, and alumina-spinel type. For the preparation of these raw materials, in addition to the Al₂O₃ source raw material and SiO₂ source raw material described above, as the magnesia source raw material, there can be used, appropriately, magnesia clinker, magnesium hydroxide, fused magnesia and the like produced according to various known methods, including natural magnesia and seawater magnesia, and as the spinel source raw material, artificial or natural spinel and the like can be used. The refractory raw materials may be blended with various cements, binders, water and the like as necessary.
[0026] When the refractory material of the present invention is used in combination with other refractory raw materials, if the blending amount of the refractory material according to the present invention is too small, there is a risk that the effects of the present invention cannot be advantageously obtained in the refractory. For this reason, when the refractory material of the present invention is used in combination with other refractory raw materials, it is preferable to use the refractory material of the present invention in an amount of 25 mass% or more relative to the total amount of the refractory material of the present invention and the other refractory raw materials.
[0027] As described in detail above, the refractory material according to the present invention is composed of a calcined product of a mixture prepared using aluminum dross. This calcined product contains Al2O3 and MgO as chemical components in predetermined proportions, while not containing a periclase phase as a crystalline phase. Due to its composition with such characteristic calcined products, the refractory material of the present invention exhibits excellent resistance to fire extinguishing as a refractory material, and when used as a refractory material for lining various containers used in aluminum casting, it exhibits excellent resistance to penetration by molten aluminum. [Examples]
[0028] The present invention will be further clarified by showing some embodiments below, but it goes without saying that the present invention is not limited in any way by the description of such embodiments. Furthermore, it should be understood that, in addition to the embodiments below and the specific descriptions above, various changes, modifications, and improvements can be made to the present invention based on the knowledge of those skilled in the art, as long as they do not depart from the spirit of the present invention.
[0029] In the following, the apparent porosity of each of the obtained refractory materials, as well as the apparent porosity of the crucibles obtained using each of those refractory materials, were measured three times according to the "boiling method" described in JIS-R-2205 (1992), and the average value was calculated to determine the apparent porosity.
[0030] -Manufacturing of fire-resistant materials 1-10- Aluminum dross and magnesium hydroxide as a source of magnesia were prepared. In order to produce refractory materials 8 to 10, aluminum dross with different impurity content (calcium oxide, silicon dioxide, and other compounds) was prepared by subjecting the aluminum dross to a predetermined treatment. These raw materials were blended in proportions to give the chemical components shown in Table 1 below, and the mixture was put into a ball mill with water and wet grinding was performed to obtain a slurry so that the average particle size of the aluminum dross was 20 μm or less. The obtained slurry was dewatered using a filter press to obtain a clay-like substance. This clay-like substance was extruded using an auger machine equipped with a round extrusion port (hole diameter: 15 mm) to produce extruded products. The produced extruded products were dried in a dryer at 110°C for 24 hours, and then fired using a rotary kiln to obtain refractory materials consisting of fired products with the chemical components shown in Table 1 below (refractory materials 1 to 10). The firing time was set to 1 hour, the firing temperature to the temperatures shown in Table 1 below for each refractory material, and both the heating rate and cooling rate were set to 300°C / h.
[0031] The calcined material obtained as described above was pulverized using a vibratory mill to a particle size of 45 μm or less. The crystalline phase of this pulverized material was measured according to powder X-ray diffraction, and glass beads were prepared using the pulverized material according to the glass bead method. The chemical components of the prepared glass beads were measured by fluorescence X-ray analysis. The content percentages of the measured crystalline phase and chemical components for each refractory material are shown in Table 1 below. On the other hand, the calcined material (refractory material) was pulverized in a pulverizer and classified using a sieve to produce four types of pulverized products consisting of coarse grain A (particle size: 5-3 mm), coarse grain B (particle size: 3-1 mm), fine grain (particle size: -1 mm), and fine powder (particle size: -200 mesh).
[0032] -Manufacturing of fire-resistant material a- Except for using calcined alumina instead of aluminum dross and magnesium hydroxide, a calcined product (refractory material a) was prepared using the same methods and procedures as for refractory materials 1 to 10, and four types of pulverized products were obtained. The calcination temperature during production, the chemical composition of the obtained calcined product (refractory material a), the apparent porosity, and the crystalline phase measured according to the above method are shown in Table 2 below.
[0033] -Manufacturing of fire-resistant materials b, c, and d- Except for using calcined alumina instead of aluminum dross, the same methods and procedures as for refractory materials 1 to 10 were used to produce calcined materials (refractories b, c, and d), and four types of pulverized products were obtained. The calcination temperature during production, the chemical composition of the obtained calcined materials (refractories b, c, and d), the apparent porosity, and the crystalline phase measured according to the above method are shown in Table 2 below.
[0034] -Manufacturing of fire-resistant material e- Except for the absence of aluminum dross and the use of magnesium hydroxide only, the calcined material was prepared using the same methods and procedures as for refractory materials 1 to 10, yielding four types of pulverized materials. The calcination temperature during production, the chemical composition of the obtained calcined material (refractory material e), the apparent porosity, and the crystalline phase measured according to the above method are shown in Table 2 below.
[0035] -Manufacturing of fire-resistant materials f and g- Except for mixing aluminum dross and magnesium hydroxide in proportions that give the chemical composition shown in Table 2 below, and using the firing temperature shown in Table 2 below, a fired material was prepared following the same methods and procedures as for refractory materials 1 to 10, and four types of pulverized materials were obtained. The firing temperature during production, the chemical composition of the obtained fired materials (refractory materials f and g), the apparent porosity, and the crystalline phase measured according to the above method are shown in Table 2 below.
[0036] The 17 types of refractory materials obtained as described above were tested for fire extinguishing properties according to the following method. Coarse grain B (particle size: 3-1 mm) of each refractory material was dried in a dryer maintained at 110°C until a constant weight was reached. Approximately 50 g of the dried coarse grain B was taken and placed in an autoclave container, where it was kept at 134°C and 3 atmospheres for 2 hours. After that, the coarse grain B was removed and dried again in a dryer maintained at 110°C until a constant weight was reached. The coarse grain B was then removed from the dryer, its appearance was visually observed, and it was evaluated according to the following evaluation criteria. ○: No disintegration or powdering of the sample (coarse grain B) due to digestion was observed at all. ×: Some degree of disintegration or powdering of the sample (coarse grain B) due to digestion is observed.
[0037] [Table 1]
[0038] [Table 2]
[0039] -Making a Crucible- Crucibles (Examples 1-16, Comparative Examples 1-6) were prepared using the pulverized products (coarse grain A, coarse grain B, fine grain, fine powder) manufactured according to the methods described above, following the procedure below. In Tables 3 to 5 below, "material" refers to "refractory material," and for example, "material 1" refers to "refractory material 1."
[0040] The crushed materials, calcined alumina, alumina cement, and dispersant shown in Tables 3 to 5 below were mixed in the proportions shown in Tables 3 to 5 below to prepare the mixed raw materials. This mixed raw material and water in the proportions shown in Tables 3 to 5 below were put into a mixer and kneaded, then poured into a designated crucible mold. After curing at room temperature for 24 hours, the mold was removed, and the removed crucible was dried in a dryer at 110°C for 24 hours to produce the desired crucible. The dimensions of the produced crucible were: outer dimensions: diameter 85 mm × height 60 mm, inner dimensions: diameter 65 mm × height 50 mm. The apparent porosity of each of the obtained crucibles was measured, and the results are shown in Tables 3 to 5 below.
[0041] The obtained crucibles were used as samples, and a penetration resistance test was performed according to the following procedure. 270g of molten Al-5Mg alloy (Al: 95% by mass, Mg: 5% by mass) was placed in a crucible and kept at 850°C for a set period (48 hours, 72 hours, 120 hours). The heating and cooling rates of the electric furnace were both set to 300°C / h. After the test, the crucibles were cut horizontally in the height direction, and the appearance of the crucibles and the cut surfaces were visually observed and evaluated according to the following evaluation criteria. The evaluation results for each crucible are shown in Tables 3 to 5. ○: No penetration of Al-5Mg alloy was observed in the crucible. △: Infiltration of Al-5Mg alloy into the crucible is observed at a penetration thickness of less than half the wall thickness of the crucible. ×: Infiltration of the Al-5Mg alloy into the crucible is observed at a penetration thickness exceeding half the wall thickness of the crucible.
[0042] [Table 3]
[0043] [Table 4]
[0044] [Table 5]
[0045] As is clear from the results in Tables 1 to 5 above, the refractory materials according to the present invention (refractory materials 1 to 10) exhibit excellent resistance to extinguishing, and the refractories (crucibles: Examples 1 to 16) made using them exhibit excellent resistance to penetration of molten aluminum alloy, regardless of the particle size of the refractory material. In contrast, i) corundum-based refractory material a and ii) refractory material b, which uses calcined alumina instead of aluminum dross as a raw material, exhibit excellent resistance to extinguishing as refractory materials, but when refractories are made using them, such refractories are found to have poor resistance to penetration of molten aluminum alloy. Furthermore, in the case of refractory materials d, e, and f, which contain periclase as a crystalline phase, the refractories obtained using them exhibit excellent resistance to penetration of molten aluminum alloy, but are found to have poor resistance to extinguishing as refractory materials.
Claims
1. It consists of a calcined product of a mixture prepared using aluminum dross, wherein the calcined product contains 60.0 to 90.0% by mass of Al as a chemical component. 2 O 3 A refractory material characterized by containing 5.0 to 30.0% by mass of MgO and not containing a periclase phase as a crystalline phase.
2. The refractory material according to claim 1, wherein the fired product is alumina-rich spinel or spinel.
3. The fire-resistant material according to claim 1 or claim 2, wherein the impurity content is 10.0% by mass or less.
4. A fire-resistant material according to claim 1 or claim 2, wherein the apparent porosity is 25.0% or less.
5. A refractory material comprising a mixture containing the refractory material described in claim 1 or claim 2.
6. In the method for manufacturing a fire-resistant material according to claim 1 or claim 2, A process to produce a slurry by wet grinding a mixture consisting of aluminum dross, a magnesia source raw material, and water, The process involves dewatering the slurry to obtain a clay-like substance, and then using this clay-like substance to produce a molded product according to an extrusion molding method. The process of drying the molded product, The process involves firing the dried molded product at 1550 to 1700°C using a rotary kiln, A method for manufacturing fire-resistant materials containing [specific material].
7. The method for producing a refractory material according to claim 6, wherein the proportion of aluminum dross in the mixture is 60 to 90% by mass.
Citation Information
Patent Citations
Method for using aluminum dross residual ash, and alumina spinel castable refractory material
JP2000263013A
Method for using aluminum dross residual ash and alumina magnesia castable refractory material
JP2000263014A
Detoxification treatment method of aluminum dross, and production method of magnesium aluminate spinel
JP2024110580A